Insights into the properties of the two enantiomers of trans-δ-viniferin, a resveratrol derivative: antioxidant activity, biochemical and molecular modeling studies of its interactions with hemoglobin. Issue 4 (17th February 2016) - Ficarra, Silvana; Tellone, Ester; Pirolli, Davide; Russo, Annamaria; Barreca, Davide; Galtieri, Antonio; Giardina, Bruno; Gavezzotti, Paolo; Riva, Sergio; De Rosa, Maria Cristina
Abstract : This study first reports the biological activity of the individual enantiomers of a resveratrol-related dimer. Abstract : Resveratrol is widely known as an antioxidant and anti-inflammatory molecule. The present study first reports the effects of trans -δ-viniferin (TVN), a dimer of resveratrol, on human erythrocytes. The antioxidant activity of TVN was tested using in vitro model systems such as hydroxy radical scavenging, DPPH and lipid peroxidation. In addition we have examined the influence of the 15 R, 22 R - and 15 S, 22 S -enantiomers (abbreviated R, R-TVN, and S, S-TVN, respectively) on anion transport, ATP release, caspase 3 activation. Given that hemoglobin (Hb) redox reactions are the major source of RBC oxidative stress, we also explored the effects of TVN on hemoglobin function. TVN showed moderate antioxidant properties and good protective activity from hemoglobin oxidation. Potential binding sites of R, R-TVN and S, S-TVN with oxy- and deoxy-Hb were also investigated through an extensive in silico docking approach and molecular dynamics calculations. The whole molecular modeling studies indicate that binding of R, R-TVN and S, S-TVN to Hb lacks of specific ligand–target interactions. This is the first report on the biological activity of the individual enantiomers of a resveratrol-related dimer.